An Enhancement of One Time Pad Based on Monoalphabeth Caesar Cipher to Secure Grayscale Image - Christy Atika Sari; Lalang Erawan; Eko Hari Rachmawanto; De Rosal Ignatius Moses Setiadi; Tan Samuel Permana (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Image is an object that has been used by various people since long ago. Utilization of these images evolve in line with advances in technology. Image in this information technology era is not only in a physical form, there is also a form of so-called digital image. Many people use digital images for personal use, so prone to be manipulated by others. Cryptographic technique, such as Caesar Cipher and OTP is a security techniques that can be applied to the digital image to avoid manipulation or theft of data image. The result is, an image can be read only by the sender and the recipient's image alone. Combined the two algorithms have fast turnaround time, up to 0.017791 seconds for the image to the size of 512x341 and 0.032302 seconds for the image to the size of 768x512. In addition, the resulting image has a very low degree of similarity, Â with the highest PSNR value obtained is 6.8653 dB. It can be concluded that the combined algorithm and OTP Caesar Cipher algorithm is fast and difficult to solve.